(3GdeSGFd GdejGaGQbjGJs - (3GdMSjfj GdbQTj, CHh GdbGSe, GdTQja GdeQJVi, Ydj Hf GdMSjf Hf ehSi Hf eMeO Hf EHQGgje, (B436 (3g`s
(3ChdgG (B:s
(3GdeSCdI GdChdi(B: (3GdUdGI LGeYI, hgd JLhR eY YOe GdehKhb HOjfg(B...s
(3BNQgG (B:s
(3hgPG GdNeS EfeG LYd YhVG dge Yf GdUObI, aEPG efYhg aj HYV GdReGf MdJ dge GdUObI eY GdefY ef gPG GdNeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B435s
(3GdCYdGe(B: (3L(B4(3, U(B278s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis